Op de bres voor het „Deutschtum“ in Limburg (1933–1940) - Brauer, Jan (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2023)
„Borders engender cultural and socio-political interaction between states. Especially in border regions, issues of nationality and identity sharpen in times of political tension. As early as 1933, for instance, Limburg faced strong influence of the rising National Socialist Third Reich, partly because of the many thousands of German migrants - ‘Rijksduitsers’ - who lived and worked there. Fierce propaganda and intimidation had to activate these so-called ‘Volksgenossen’, but in addition, the Limburgers, as ‘race-Germans’, also belonged in this Reich, according to Berlin. They had strayed from Deutschtum and had to be reclaimed with the use of propaganda. This early invasive socio-political influence process – a clear prelude to the occupation years ‘40-45’ – is examined in this article from German and Dutch sources. What was the impact on the daily lives of border residents, who traditionally fostered close ties with neighbours across the border? To answer this question, this article presents new cross-border regional research in the periphery of Limburg as a contribution to the broader historiography of Dutch WWII-history.“
Keywords: Grenzgebiet; Nationalsozialismus; Provinz Limburg (Niederlande)

„Die Annexionsfrage steckt voller Minen“. Briefe an die Annexatie-Enquête-Commissie der Werkgemeenschap Limburg, 1945 - Haude, Rüdiger (Dies- und jenseits der Grenze. Translokale Prozesse und ihre Einwirkung auf den deutsch-niederländischen Grenzraum, 2017)
Keywords: Annexion; Grenzgebiet; Provinz Limburg (Niederlande); Selfkant

Liefde met en zonder grenzen. De geografische horizon van huwelijkspartners in Limburg in de negentiende en vroege twintigste eeuw - Ekamper, Peter; Poppel, Frank van (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2012)
Keywords: Binationale Ehe; Binationales Ehepaar; Ehepaar; Kulturkontakt; Provinz Limburg (Niederlande)

Annexatie en regionale identiteit. De Annexatie-Enquête van de Werkgemeenschap Limburg in 1945 - Haude, Rüdiger (Studies over de sociaal-economische geschiedenis van Limburg. Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2012)
Keywords: Annexion; Grenzgebiet; Provinz Limburg (Niederlande); Selfkant

Last Chance. Belgium at Versailles - Tuyll, Hubert P. van (Boundaries and their meanings in the history of the Netherlands, 2009)
Keywords: Annexion; Erster Weltkrieg; Grenzgebiet; Luxemburg; Ostbelgien; Provinz Limburg (Niederlande); Seeländisch-Flandern; Versailler Vertrag (1919)

Werken over de grens. Limburgers naar Duitsland, 1870–1914 - Langeweg, Serge (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2002)
Keywords: Arbeitsmarkt; Arbeitsmigration; Deutschland; Grenzarbeitnehmer; Provinz Limburg (Niederlande)